Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

If 3t − 7 = 5t , then 6t = how do you solve this

Sagot :

[tex]3t-7=5t\\ 5t-3t=-7\\ 2t=-7|\cdot3\\ \boxed{6t=-21} [/tex]
naǫ
[tex]3t-7=5t \ \ \ |\hbox{subtract 3t} \\ -7=5t-3t \\ -7=2t \ \ \ |\hbox{multiply by 3} \\ \boxed{6t=-21}}[/tex]